Impact of Patient Demographic Factors on Preoperative Patient-Reported Outcomes Measurement Information System (PROMIS) Physical Function, Pain Interference, and Depression Computer Adaptive Testing Scores in Patients Undergoing Shoulder and Elbow Surgery. Issue 11 (22nd November 2019) - Meldau, Jason E.; Borowsky, Peter; Blanchett, Jacob; Stephens, Jeffrey; Muh, Stephanie; Moutzouros, Vasilios; Makhni, Eric C.
Background: There has been a growing emphasis in orthopaedics on providing patient-centered care. The US National Institutes of Health launched the Patient-Reported Outcomes Measurement Information System (PROMIS) initiative that incorporates patient-reported outcome measures across a number of medical domains. The relationship between PROMIS domains and the impact of patient demographic factors in those undergoing upper extremity surgery remains unclear. Purpose/Hypothesis: The goal of this study was to investigate the correlation between physical function, pain interference, and depression in patients undergoing shoulder and elbow surgery as measured by PROMIS computer adaptive testing (CAT) forms and to determine the impact of patient demographic factors. We hypothesized that there would be a significant negative correlation between physical function and both pain interference and depression in this patient population. Study Design: Cross-sectional study; Level of evidence, 3. Methods: All patients who underwent elective shoulder or elbow surgery by 3 shoulder, elbow, and/or sports medicine fellowship–trained orthopaedic surgeons were included in the study. Preoperative PROMIS–Upper Extremity (PROMIS-UE), PROMIS–Pain Interference (PROMIS-PI), and PROMIS-Depression (PROMIS-D) CAT scores were analyzed. Pearson correlations were calculated between PROMIS domains as well as between PROMIS outcomes with patient demographic factors. Results: Preoperative PROMIS CAT scores for all 3 domains were collected and analyzed from 172 unique patients (516 individual CAT forms) with shoulder and elbow injuries. A negative correlation of moderate strength was found between the PROMIS-UE and PROMIS-PI ( R = –0.61; P < .001), and a negligible correlation was found between the PROMIS-UE and PROMIS-D ( R = –0.28; P < .001). When stratified by patient demographic factors, the correlation between the PROMIS-UE and PROMIS-PI was stronger in female patients compared with male patients ( R = –0.77 vs –0.46, respectively; P < .001 for both), stronger in black patients compared with white patients ( R = –0.72 vs –0.56, respectively; P < .001 for both), and highest in current tobacco users ( R = –0.80; P < .001). Conclusion: Before shoulder and elbow surgery, patients demonstrated impairments in physical function and pain interference as measured by CAT forms, with a moderate negative correlation between baseline upper extremity physical function and pain interference scores. In certain subpopulations, such as female patients, black patients, and current tobacco users, the correlations between these tested domains were stronger than in other groups.